COMPARATIVE ASSESSMENT OF SAFETY OF EPIDURAL CAVITY PARACENTESIS THROUGH MEDIAN AND PARAMEDIAN ACCESS - V. V. Kobrina; V. P. Kobrin; V. A. Glusсhenko (Вестник анестезиологии и реаниматологии)
The technique has been developed to evaluate the safest conditions of epidural anesthesia depending on the level of paracentesis, access and needle size. The technique is oﬀered for calculation of the safe area allowing evaluating the chances of adverse events depending on the applied access.